Transmissão de vídeo em redes mesh usando NS3 e evalvid com provisionamento de qualidade de experiência - PEREIRA, Ronilson Williame da Silva (2019)
This work was done with the Quality Method of a user-qualified experience, based on the assessment of the quality of the video transmitted in a network using an application as a client server, with the objective of evaluating the evaluation videos of the mathematical tools to make this assessment. For this, a bibliographical research was chosen to respect the objective metrics to make an evaluation of the quality of experience. In order to perform the simulation, we used the NS-3 network simulator with the evaluation framework, using models of mobilization in areas of the city of castanhal. These videos are based on objective metrics: Signal-to-Noise Ratio (PSNR), Structural Similarity Index (SSIM) and Video Quality Measurement (VQM). The present work was carried out from the collection of data searched in Internet databases, and the data were collected according to the objectives of the work. As a result of the analysis it could be that the videos are tried in the simulation in low degradation.